Experimental study and modeling of bubble lift-off diameter in subcooled flow boiling including the inclination effect of the heating surface. Issue 11 (2nd November 2021) - Rafiq Akand, M.A.; Kitahara, Kei; Matsumoto, Tatsuya; Liu, Wei; Morita, Koji
ABSTRACT: In-vessel retention (IVR) is a viable method of preserving reactor pressure vessel integrity in severe reactor accidents. Accurate knowledge of the bubble lift-off diameter for a downward-facing inclined heating surface is vital for successfully implementing IVR following the critical heat flux (CHF). A research facility was designed to visualize bubble lift-off for different heating surface orientations from downward-facing horizontal to vertical in IVR and experimentally determined the bubble lift-off diameter. A significant effect of inclination angle on lift-off diameter was found. The maximum lift-off diameter was achieved in the downward-facing horizontal position of the heating surface, whereas the minimum one was with vertical orientation. The existing lift-off models of Sugrue et al. and Situ et al. follow the experimental data parametrically, but with significant average errors of 51.99% and 102.08%, respectively. These models either ignore bubble sliding velocity or assume it is constant with respect to the local liquid velocity. An improved mechanistic model is proposed considering the bubble velocity as a dynamic variable for the lift-off diameter including the inclination effect of the heating surface, and it predicts the experimental data with a mean relative error of 9.89%.